Health risk assessment total mercury in locally caught yellowfin and frigate tuna in Eastern Visayas and commercial canned tuna. - Pacoma, Arvin U.; Yap-Dejeto, Leni G. (Arvin U. Pacoma, 2018)
Mercury is a toxic trace metal, which can accumulate to levels threatening humans and other organisms. In Japan, the United States of America and Spain, mercury concentrations in fresh and canned tuna is monitored for food safety. But in the Philippines, the levels of this toxic heavy metal remain unknown both in locally caught and canned tuna. The total mercury concentrations in Yellow fin (Thunnus albacores), Frigate (Auxis thazard thazard) tuna caught in Eastern Visayas and canned tuna were determined by Inductively Coupled-Plasma Optical Emission Spectrometry. The total mercury concentrations measured from nine Frigate and three Yellow fin tuna and four canned tuna test samples were 0.026 mg/kg, 0.001 mg/kg and 0.07 mg/kg respectively. Estimated daily intake assessment for neurological effects associated with the consumption of the tuna species and canned tuna was done. Daily intake for normal Filipino adult male for locally caught tuna is 5.98 kilograms or 41.59 kilograms weekly; whereas for canned tuna, it is 0.180 kg or one can per day.
A research paper (B.S. Biology) -- University of the Philippines, Tacloban.